Does Intra-party Democracy Enhance Party Digitalisation? Evidence from the Spanish Socialist Workers‘ Party (2014–2024) - Alberto Díaz-Montiel (Acta Politologica)
In recent times, political parties have increased the options for their members to participate in their decision-making processes. The widespread use of the internet has facilitated this process, affecting the parties’ organisational structures. The article analyses how the digitalisation of the Spanish Socialist Workers’ Party (PSOE) has been affected by the introduction of two new options for internal democracy: primary elections to choose its leader and consultations with its members. The research period begins in 2014, when for the first time this party elected its general secretary through primary elections and analyses the state level of this organisation. The article argues that while the PSOE has introduced new tools for internal participation, these have not allowed for a significant increase in its digitalisation.